BK Channel in the Physiology and in the Cancer of Pancreatic Duct: Impact and Reliability of BK Openers - Zuccolini, Paolo; Gavazzo, Paola; Pusch, Michael (Frontiers in Pharmacology, 2022)
BK (KCa 1.1, Slo-1) is a K+ channel characterized by an allosteric regulation of the gating mechanism by Ca2+ binding and voltage, and a high unitary conductance. The channel is expressed in many different tissues, where it is involved in the regulation or the fine-tuning of many physiological processes. Among other organs, BK is expressed in the pancreatic duct, a part of the gland important for the correct ionic composition of the pancreatic juice. Unfortunately, the pancreatic duct is also the site where one of the deadliest cancer types, the pancreatic duct adenocarcinoma (PDAC), develops. In the past years, it has been reported that continuous exposure of cancer cells to BK openers can have a significant impact on cell viability as well as on the ability to proliferate and migrate. Here, we first summarize the main BK channel properties and its roles in pancreatic duct physiology. Then we focus on the potential role of BK as a pharmacological target in PDAC. Moreover, we discuss how results obtained when employing BK activators on cancer cells can, in some cases, be misleading.